2021
DOI: 10.3390/jcm10092006
|View full text |Cite
|
Sign up to set email alerts
|

Can a Single Trial of a Thoracolumbar Myofascial Release Technique Reduce Pain and Disability in Chronic Low Back Pain? A Randomized Balanced Crossover Study

Abstract: Although manual therapy for pain relief has been used as an adjunct in treatments for chronic low back pain (CLBP), there is still the belief that a single session of myofascial release would be effective. This study was a crossover clinical trial aimed to investigate whether a single session of a specific myofascial release technique reduces pain and disability in subjects with CLBP. 41 participants over 18 years old were randomly enrolled into 3 situations in a balanced and crossover manner: experimental, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The characteristics of the 17 meta‐analysed studies are summarized in Table 1 and the text below. One trial (Paulo et al., 2021) was a cross‐over design, all others were parallel‐group RCTs. Most trials (84%) were single‐centre trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the 17 meta‐analysed studies are summarized in Table 1 and the text below. One trial (Paulo et al., 2021) was a cross‐over design, all others were parallel‐group RCTs. Most trials (84%) were single‐centre trials.…”
Section: Resultsmentioning
confidence: 99%
“…Participants were reported as supposed to be blinded to group allocation in nine control intervention arms (53%) (Amirova et al, 2017;Bialosky et al, 2014;Cerritelli et al, 2015;Chaibi et al, 2017;Ince et al, 2023;Loose et al, 2021;Moraska et al, 2017;Schmidt et al, 2011;Sisman & Arslan, 2022). Blinding was not an objective in five control intervention arms (29%) (Ashar et al, 2022;Hasuo et al, 2022;Krauß et al, 2014;Ozgul et al, 2023;Paulo et al, 2021), one of which only blinded participants to another active comparator, not the main investigational treatment (Krauß et al, 2014). Blinding information could not be obtained for another three trials (18%) (Allen et al, 2010;Hensel et al, 2015;Licciardone et al, 2010).…”
Section: Control Interventions and Blindingmentioning
confidence: 99%
“…7 When TLF occurs, it causes LBP and affects the movement and sensory function of the body. 8,9 Although there have been many studies on the mechanism and pathological changes of TLF, the understanding of TLF is not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no consensus on the frequency or number of treatments necessary with MFR, regardless of the reason for which they are used, for example: chronic low back pain, fibromyalgia, functional capacities… [39,40]. Whatever the modality of application (massage or osteopathic manual therapy) or location (lower limb or trunk) it seems that only one MFR session have a limited or even non-existent effect on balance [41,42] while recent studies have shown that two sessions can [43,44].…”
Section: Introductionmentioning
confidence: 99%